Analysis of the impact of the use of and of climate on the vulnerability and availability of Macaranga beillei in Côte d’Ivoire (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Jean KK, Francis YN, Fatou T, Moussa K, Bakayoko A, Bogaert J. 2022. Analysis of the impact of the use of and of climate on the vulnerability and availability of Macaranga beillei in Côte d’Ivoire. Biodiversitas 23: 5396-5405. Macaranga beillei Prain is a vulnerable species of the Euphorbiaceae family, used in traditional medicine, and whose habitat is threatened by anthropogenic activities. This study is a contribution to the knowledge of the causes of the threat of this species in Côte d'Ivoire. The database used includes data from the SIG IVOIRE database (Gautier et al. 1999), the flora of Côte d'Ivoire (Aké Assi 2001), the GBIF website (Global Biodiversity Information Facility, wwwgbif.org) and the Paris Museum website (http://www.mnhn.fr/fr/collection). The QGIS software (Quantum GIS) version Lyon 2.12.3. and the MaxEnt (Maximum Entropy) model was used to produce potential distribution maps for the periods 1950-2000 and 2000-2050. A questionnaire was developed for the ethnobotanical survey. It emerges from this analysis that the Banco National Park is the most sampled locality with 38 samples out of 72, i.e. a rate of 52.77%. The value of the species vulnerability risk index (VI) is 2.46. In 2050, the range of the species will decrease by 6,696.127 km². The assessed extent of occurrence (EOO) and area of occupancy (AOO) values are 5,848.921 km² and 72.000 km² respectively. These results confirm that M. beillei is a vulnerable species.